Different twig litter (Salix caprea) diameter does affect microbial community activity and composition but not decay rate - Angst, Šárka; Baldrian, Petr; Harantová, Lenka; Cajthaml, Tomáš; Frouz, Jan (FEMS microbiology ecology, 2018)
Small twigs represent a substantial input of organic carbon into forest soils, but potential influencing factors on their decomposition have rarely been investigated. Here, we studied potential effects of twig size on decomposition and associated composition and activity of microbial communities during decomposition. Because the surface area for microbial colonization and the volume of accessible substrate increases with decreasing twig size, we hypothesized that twig size affects both microbial community and decomposition rate. Litterbags with twigs (Salix caprea) of two different diameters were placed within the litter layer and consecutively collected over a seven-year period. We determined the mass loss and microbial measures after each sampling event. The observed microbial parameters suggested a faster microbial colonization of thin twigs, where the proportion of bacteria was higher than in thick twigs. The development of the microbial community in thick twigs was more gradual and the proportion of fungi was higher. Despite this differential and successional development of microbial communities (and against our hypothesis), the mass loss among different twig diameters did not differ after our seven-year experiment, indicating that surface-to-volume ratios, though a primary control on microbial succession, may have limited predictive power for twig decomposition rates.
Keywords: půdní mikrobiologie; Forests; Fungi; mikrobiota; Salix; Soil; půda; Microbiota; Plant Leaves; Bacteria; houby; listy rostlin; Soil Microbiology; lesy